2016
DOI: 10.15845/voices.v16i1.842
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Dialogue in Music Therapy: A Hermeneutical Analysis of Three Music Therapy Sessions

Abstract: Verbal dialogue is often a main component of music therapy sessions, however, it is seldom discussed in the music therapy literature. This qualitative study examined three music therapy sessions arranged especially for research purposes. Video recordings of these sessions were analysed as well as interviews with the music therapists conducting the sessions. Specific verbal interventions used during the sessions included: questions, repetition and other types of commenting phrases, silence, paradoxes and rephra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…These skills have been used to facilitate verbal processing of thoughts, behaviors, and emotions (Amir, 1999;Gardstrom, 2001;Grocke & Wigram, 2007;Linblad, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These skills have been used to facilitate verbal processing of thoughts, behaviors, and emotions (Amir, 1999;Gardstrom, 2001;Grocke & Wigram, 2007;Linblad, 2016).…”
mentioning
confidence: 99%
“…For music therapists practicing from a music-centered or music as therapy perspective, music is the catalyst for change. Music serves as the medium through which therapeutic issues are accessed, addressed, and resolved (Ansdell, 1999;Bruscia, 1998a;Gardstrom, 2001;Linblad, 2016), and verbal components are typically limited to social interactions and assessment of the therapeutic progress (Gardstrom, 2001;Grocke & Wigram, 2007;Guerrero, Marcus, & Turry, 2015). However, some musiccentered models like Analytic Music Therapy incorporate verbal interventions to communicate ideas, share insight, and make interpretations (Amir, 1999;Bruscia, 1988).…”
mentioning
confidence: 99%
“…The dearth of literature and resources on the topic of verbalisation in music therapy has been highlighted by previous authors (Lindblad, 2016;Schwartz, 2019). Grocke and Wigram (2007) suggested that comprehensive training in counselling skills was not necessary for music therapists but stressed that some basic skills could equip practitioners when exploring and processing music experiences with their clients.…”
Section: Intr Introduction Oductionmentioning
confidence: 97%
“…This paper presents an exploratory investigation of issues relating to music therapists' understandings of verbal dialogue and the perceived benefits and challenges of engaging in verbal dialogue with clients. Basic counselling or communication skills have an established place throughout many music therapy sessions, specifically to: open and close sessions, gather information and provide feedback about clients' musical experiences, establish trust, and to facilitate genuine encounters (Grocke & Wigram, 2007;Lindblad, 2016). However, the applicability of verbal interaction remains a divisive topic within the literature (Aigen, 2014), with some authors arguing that the thera-peutic impact of musical engagement may be diminished if processed through higher cognition.…”
Section: Intr Introduction Oductionmentioning
confidence: 99%
See 1 more Smart Citation